Hubungan Pengetahuan Ibu terhadap Kejadian Karies pada Anak PAUD Qalby Play School Kab. Bogor - Faradillah Usman; Fidzah Nur Fajrina Murad; Wirda Aulia; Nurul Fatimah (Jurnal Sains dan Kesehatan, 2026)
Dental caries is one of the most common oral health problems among young children. Preschool-aged children are highly dependent on their parents, especially mothers, for dental health care. A mother's level of knowledge is expected to influence the incidence of caries in children. Purpose: This study aims to determine the relationship between maternal knowledge and the incidence of dental caries among children at Qalby Play School, Bogor Regency. Method: This research employed a cross-sectional design with an analytic survey approach. The population consisted of all mothers and their children at Qalby Play School, totaling 30 participants, selected using total sampling. Data were collected using questionnaires to assess maternal knowledge and odontogram sheets to measure caries incidence. Data were analyzed using univariate and bivariate analysis with the Chi-square test. Result: The results showed a significant relationship between maternal knowledge and the incidence of dental caries in children, with a p-value 0,047 < 0,05. Conclusion: There is a statistically significant relationship between maternal knowledge and the incidence of dental caries in children. Therefore, it is important for parents, especially mothers, to pay close attention to their children's oral health by ensuring proper and regular tooth brushing and scheduling dental check- ups every six months.